KONFLIK POLITIK DALAM NOVEL SAIGO NO SH?GUN KARYA RYOTARO SHIBA - Suargita, I Wayan (Humanis, 2016)
This study discussed political conflict of the Bakumatsu era and the writer 's view that is reflected in the novel Saigo no Shogun created by Ryotaro Shiba. The method used in this study were historical and descriptive analysis method s . The theory used were the theory of New Historicism by Peter Barry, conflict theory by Ralf Dahrendorf, and structuralism-genetic by Lucien Goldmann. The results showed that there are four political conflicts include (1) Ansei no Taigoku, (2) Ikedaya Jiken, (3) Hyogo port opening conflict, (4) and Toba-Fushimi no Tatakai. These conflicts are mainly due to the opening of Japan by foreign nations that lead to Japan’s political, economic, and social situations were crisis. World writer’s view of political conflict in Bakumatsu era, namely: (1) the importance of Japan’s modernization, (2) changes should be made jointly, and (3) the self quality of Tokugawa Yoshinobu.
Keywords: political conflict, the writer’s view, bakumatsu